2013
DOI: 10.1098/rsif.2013.0139
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interface between adsorbed fibronectin and human embryonic stem cells

Abstract: The cell-substrate interface plays a key role in the regulation of cell behaviour. Defining the properties of this interface is particularly important for human embryonic stem (hES) cell culture, because changes in this environment can regulate hES cell differentiation. It has been established that fibronectincoated surfaces can promote the attachment, growth and maintenance of the undifferentiated phenotype of hES cells. We investigated the influence of the surface density of adsorbed fibronectin on hES cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…Furthermore, different cell types were known to respond differently to the amount of surface-bound fibronectin. For instance, endothelial cell and embryonic stem cell were reported to adhere better on surfaces with higher fibronectin adsorption [55][56], while another study indicated that MG63 (human osteosarcoma) cells preferably adhered to surfaces with lower fibronectin adsorption [57]. To date, BMSC adhesion under varying fibronectin adsorption is still poorly understood.…”
Section: Rowlands Et Al Evaluated the Adhesion And Spreading Of Bmscmentioning
confidence: 99%
“…Furthermore, different cell types were known to respond differently to the amount of surface-bound fibronectin. For instance, endothelial cell and embryonic stem cell were reported to adhere better on surfaces with higher fibronectin adsorption [55][56], while another study indicated that MG63 (human osteosarcoma) cells preferably adhered to surfaces with lower fibronectin adsorption [57]. To date, BMSC adhesion under varying fibronectin adsorption is still poorly understood.…”
Section: Rowlands Et Al Evaluated the Adhesion And Spreading Of Bmscmentioning
confidence: 99%
“…To quantify FN on different substrates, fluorescent intensity was measured modifying previously reported method by Kalaskar et al 12 In addition, presence of immobilized FN (10 mg mL 21 ) was confirmed with anti-FN antibody (Cat. EDC-NHS coupling of L-lysine (1 mg mL 21 , Sigma) was confirmed with FT-IR.…”
Section: Stability Of Immobilized Ecmmentioning
confidence: 99%
“…During the earliest stages of development, integrin subunits α5 and αv bind to laminin and fibronectin . These subunits, along with ÎČ1 and ÎČ5, are important in ESC self‐renewal and maintaining the pluripotent phenotype . As cells differentiate, the integrin profile changes, and consequently the cell's response to extracellular force changes.…”
Section: Cell Response To Mechanical Stressmentioning
confidence: 99%